2023
DOI: 10.1186/s12909-022-03977-5
|View full text |Cite
|
Sign up to set email alerts
|

Eleven years of data on the Jefferson Scale of Empathy – medical student version: Japanese norm data and tentative cutoff scores

Abstract: Background More and more studies investigate medical students’ empathy using the Jefferson Scale of Empathy (JSE). However, no norm data or cutoff scores of the JSE for Japanese medical students are available. This study therefore explored Japanese norm data and tentative cutoff scores for the Japanese translation of the JSE-medical student version (JSE-S) using 11 years of data obtained from matriculants from a medical school in Japan. Methods Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Establishing cut-off points is essential for identifying medical students with low empathy, with the ultimate goal of implementing curricular interventions to enhance their empathy according to their specific needs, either as a whole or individually [ 40 , 41 ]. Cut-off points may be different in different cultural contexts [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing cut-off points is essential for identifying medical students with low empathy, with the ultimate goal of implementing curricular interventions to enhance their empathy according to their specific needs, either as a whole or individually [ 40 , 41 ]. Cut-off points may be different in different cultural contexts [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hojat and Gonnella conducted a study and suggested low and high tentative cut-off scores for male students of ≤96 and ≥127, respectively, and low and high scores for female students of ≤102 and ≥129, respectively [ 42 ]. Kataoka et al conducted a study with Japanese medical school matriculants and suggested low and high cut-off scores for male students of ≤91 and ≥126, respectively, and low and high scores for female students of ≤97 and ≥128, respectively [ 40 ].…”
Section: Methodsmentioning
confidence: 99%